Chloride and Acetonitrile Ruthenium(IV) Complexes: Crystal Architecture, Chemical Characterization, Antibiofilm Activity, and Bioavailability in Biological Systems - Agnieszka Jabłońska-Wawrzycka; Patrycja Rogala; Grzegorz Czerwonka; Maciej Hodorowicz; Justyna Kalinowska-Tłuścik; Marta Karpiel (Molecules)
Due to the emergence of drug resistance, many antimicrobial medications are becoming less effective, complicating the treatment of infections. Therefore, it is crucial to develop new active agents. This article aims to explore the ruthenium(IV) complexes with the following formulas: (Hdma)2(HL)2[RuIVCl6]·2Cl·2H2O (1), where Hdma is protonated dimethylamine and L is 2-hydroxymethylbenzimidazole, and [RuIVCl4(AN)2]·H2O (2), where AN is acetonitrile. This paper delves into the physicochemical characteristics and crystal structures of these complexes, employing various techniques such as spectroscopy (IR, UV–Vis), electrochemistry (CV, DPV), and X-ray crystallography. Hirshfeld surface analysis was also performed to visualize intermolecular interactions. Furthermore, the potential antibiofilm activity of the complexes against Pseudomonas aeruginosa PAO1 was investigated and the effect of the compounds on the production of pyoverdine, one of the virulence factors of the Pseudomonas strain, was assessed. The results show that particularly complex 1 reduces biofilm formation and pyoverdine production. Additionally, the bioavailability of these complexes in biological systems (by fluorescence quenching of human serum albumin (HSA) and molecular docking studies) is discussed, assessing how their chemical properties influence their interactions with biological molecules and their potential therapeutic applications.